An Insight to How Estate Women in Sri Lanka Manage Abnormal Vaginal Discharge - Ilankoon IMPS; Goonewardena CSE; Fernandopulle RC; Perera PPR (Tehran University of Medical Sciences, 2017)
An Insight to How Estate Women in Sri Lanka Manage  Abnormal Vaginal Discharge